The Relationship between Corporate Governance Quality and Firm Performance: The Moderating Role of Capital Structure - Marwan Mansour (15944825) (2023)
This study aims to explore whether capital structure (CS) has a contingent role in the relationship between corporate governance (CG) quality and firm performance. The empirical findings indicate that CG quality had a positive and significant effect on the performance of Jordanian non-financial firms listed on the Amman Stock Exchange (ASE) from 2014 to 2019. Additionally, the moderate effect of the CS reinforces this relationship. These results are robust to alternative econometric specifications and variable definitions. This study utilizes certain firm-specific characteristics to represent the CS to assess its role as a moderating variable in the relationship between CG quality and firm performance. This study makes a contribution to the literature by showing that CS can strengthen the relationship between CG quality and firm performance. The results have important managerial implications for the practice of CG in developing countries. Firms in developing countries can enhance performance by implementing and abiding by good governance practices. Moreover, firms in developing countries should adopt effective financial strategies regarding CS to enhance the relationship between CG quality and firm performance. Finally, potential investors should consider the debt level in the CS of non-financial firms in Jordan when making investment decisions. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/su141710525